Wide bandgap OPV polymers based on pyridinonedithiophene unit with efficiency >5%1. Issue 8 (14th August 2015) - Schneider, Alexander M.; Lu, Luyao; Manley, Eric F.; Zheng, Tianyue; Sharapov, Valerii; Xu, Tao; Marks, Tobin J.; Chen, Lin X.; Yu, Luping
<x xml:space="preserve">Abstract</x> We report the properties of a new series of wide band gap photovoltaic polymers based on the N-alkyl 2-pyridone dithiophene (PDT) unit.